2018
DOI: 10.1002/pon.4630
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and oncologists' views on family involvement in goals of care conversations

Abstract: Patients and oncologists have similar views about family involvement in GoC conversations. Learning how to communicate with family members should be a critical component of physician education in palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Over time, our findings indicated a change in the relationship between patients, and their caregivers with patients preferring to confide issues pertaining to the cancer with likeminded, rather than caregivers. The patients described a feeling of wanting to protect those close to them from further uncertainty and worry, as also found in a previous study [23]. A recent focus group study of patients and caregivers likewise found that changes in the roles between patients and caregivers may lead to relationship challenges during the treatment trajectory [24].…”
Section: Discussionsupporting
confidence: 71%
“…Over time, our findings indicated a change in the relationship between patients, and their caregivers with patients preferring to confide issues pertaining to the cancer with likeminded, rather than caregivers. The patients described a feeling of wanting to protect those close to them from further uncertainty and worry, as also found in a previous study [23]. A recent focus group study of patients and caregivers likewise found that changes in the roles between patients and caregivers may lead to relationship challenges during the treatment trajectory [24].…”
Section: Discussionsupporting
confidence: 71%
“…We report findings on other interview content elsewhere. 7,8 We continued interviewing until we achieved data saturation. We asked oncologists to complete demographic/practice information forms.…”
Section: Methodsmentioning
confidence: 99%
“…However, apart from the benefit of family involvement, there can also be some challenges to these conversations. Some studies demonstrated discrepancies between patient-family, and family-physician understanding about treatment goals in advanced cancer [42] . For example, a study conducted by Lipson et al [47] with 41 patient-family caregiver dyads demonstrated that patients and their family members might have different preferences for quality or length of life.…”
Section: Patients' Preferences Regarding Family Involvement In Decisimentioning
confidence: 99%
“…Oncologists recognize the importance of family involvement in decisions near the end of life. A qualitative interview study with 38 patients with advanced cancer and their oncologists (n = 21) found that patients and oncologists shared similar views about family involvement in such decisions, highlighting the importance for patients' understanding of their disease and family emotional support [42] . However, clinical evidence demonstrates that oncologists are still reluctant to involve family or else involve them too late in the course of the disease [43][44][45] .…”
Section: Patients' Preferences Regarding Family Involvement In Decisimentioning
confidence: 99%
See 1 more Smart Citation